Teaching Security in Electronic Transactions through Indonesian Language Materials in High Grade of Elementary School Students - Ferril Irham Muzaki (JKTP: Jurnal Kajian Teknologi Pendidikan, 2018)
The purpose of this research is to find out the security patterns in the internet world. To secure electronic transactions, students in primary schools are taught to have an understanding of methods and techniques for comfortable electronic transactions, and have the ability to control the existence of information stored in electronic information. The method of this study uses (1) interviews with electronic transaction experts, (2) study and literature review, and (3) phenomenological studies. Data from the three results are combined for later synthesis as material for discussion. Based on the study above, it was found that, (1) it is necessary to open up insights for elementary school students about the public sphere and the private sphere, (2) students in primary schools need to be given insight into the techniques of securing self-owned information in public spaces, and (3) need to be invested in elementary school students to make electronic transactions as needed. The conclusions of this study are that students in elementary schools need to be understood about the electronic world. It is recommended for teachers to begin introducing the impact of electronic transactions in the learning environment of elementary school students.Keywords: electronic transactions, information, network security, cyber security